Risk Factors for Surgical Site Infection following External Fixation and Osteosynthesis of Patients with Tibial Plateau Fracture - Forni, José Eduardo N.; Rabesquine, Caio Henrique N.; Jalikj, Wahi (The Journal of Knee Surgery, 2025)
Tibial plateau fractures account for approximately 1% of all fractures and normally occur as low- or high-energy injuries. This study aims to assess risk factors for site infection following external fixation and osteosynthesis of patients with tibial plateau fracture. A retrospective study was conducted involving the records of patients with Schatzker types I, II, III, IV, V, and VI tibial plateau fractures submitted to external fixation by the emergency ward staff, followed by internal fixation with definitive osteosynthesis after improvement of the soft tissues by the knee surgery team. The following data were collected: energy of fracture, presence/absence of exposed fracture, time between injury and emergency care, time between external fixation and definitive osteosynthesis, comorbidities, number of access routes, duration of surgery, number of participants in surgery, type of surgeon (resident or professor), distance from Schanz screws to focus of the fracture, type of fracture according to the Schatzker classification, and patient age. Among the 137 patients studied, mean age was 43.4 ± 13.8 years, 72.9% were male, 5.1% had diabetes; 43% had Schatzker VI tibial fracture; 82.4% of the fractures were caused by high-energy trauma; 90.5% had closed fractures; 100% used an external fixator prior to definitive osteosynthesis; and 49.6% had dual surgical access (medial and lateral). The prevalence of infection at the surgical site was 19.7%. In the comparison of patients with and without infection, a significant difference was found in the distance between the Schanz screws and focus of fracture (p = 0.0093), which was smaller in patients with infection at the surgical site. A longer time of external fixator use was also associated with the occurrence of infection at the surgical site (p = 0.0283). In conclusion, the positioning of Schanz screw that is an important factor for infection of surgical site, with risk of infection higher in individuals with screws closer to the focus of fracture. Duration of external fixator use may also increase risk of infection after definitive osteosynthesis.
Keywords: tibial plateau fractures; treatment; external fixation; definitive osteosynthesis; infection